Recurrent biliary pancreatitis associated with analyzed biliar localization vesicle And interauricular communication: Pancreatitis biliar recurrente asociada a vesícula biliar de localización anómala y comunicación interauricular. - Soto, Alonso (2019)
A 32-year-old woman admitted to the medical service with a clinical picture of recurrent biliary pancreatitis and symptomatic cholelithiasis. Abdominal ultrasound and cholangioresonance showed a gallbladder in an unusual position (posterior) and an anomaly of the biliary tree. Incidentally, the presence of an atrial septal defect associated with signs compatible with pulmonary hypertension is evident. We have not found in the literature an association between the presence of this gallbladder abnormality and the presence of atrial or other congenital heart disease.